Penggunaan Media Sosial Terhadap Kegiatan Pemasaran Dalam Memasarkan Produk Mokko Factory Kota Sukabumi - Cici Hestia; Ce Gunawan (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
The use of social media that is rife in the community has made many companies market their products on social media. The formulation of the problem raised in this research is the role of social media for the Mokko Factory company, the company in conducting sales and promotions through social media and the role of social media in marketing strategies and responses from various groups. The purpose of this study is to find out how the role of social media for companies in Mokko Factory marketing activities, the role of social media in marketing strategies, the responses of lecturers and students to social media as a means of promotion and to find out how the advantages and disadvantages of using social media as a means of promoting Mokko Factory. The research method used for this research is a qualitative method, namely research on research that is descriptive and tends to use analysis. The result of this study is that knowing the role of social media for companies is very profitable because it makes marketing easier.